IFRS convergence impact on audit fee determinants: evidence from Indonesia - Kusmanto, Michael Aditya (2022)
Indonesia had made a public commitment back in 2008 to converge the Indonesian Accounting Standard (SAK) with that of IFRS. IFRS convergence was done in stages and the new standards were introduced and updated one at a time throughout the years. As at 2012, the SAK was equivalent to IFRS standards in 2009, leading to a 3 years gap although at 2015 this gap was reduced to 1 year. The aim of this study is to identify the key determinants of audit fee for listed companies in Indonesia post convergence. Since the convergence took place in stages this research also aims to study the difference in audit fee determinants in the different phases of convergence. Sample from non-financial companies listed in the Indonesian stock exchange from 2011 to 2019 revealed that 188 companies disclose their audit fee regularly in their annual and/or financial report which resulted in 1692 firm-years. The findings reveal that net assets, cash, subsidiary, type of auditor, and sharia compliance are all significant determinants of audit fee. Key audit fee determinants such as net assets, subsidiary and type of auditors had a differing impact on audit fee in phase 1 and phase 2. This contributes in providing a better understanding of audit fee determinants particularly post convergence which can be used as reference for companies in deciding whether audit firms are justified when they bill their clients. The study particularly contributes in the understanding of auditors’ view of Shariah compliance, which is supposedly an additional governance element and helps to reduce business risks. Several key implications arise from this project which are discussed.